2016
DOI: 10.5152/balkanmedj.2016.15052
|View full text |Cite
|
Sign up to set email alerts
|

Osteoma and Ectopic Tooth of the Left Maxillary Sinus: A Unique Coexistence

Abstract: Background: Ectopic eruption of a tooth or osteoma rarely occurs within the maxillary sinus. Coexistence of these two rare entities in the maxillary sinus has never been reported in the English literature. Case Report: Herein, we present a 21 year-old male patient with osteoma and ectopic tooth in the left maxillary sinus treated with the removal of the ectopic tooth by endoscopic sinus surgery and excision of the osteoma by the CaldwellLuc procedure. Conclusion: Unique coexistence of two different entities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Maxillary sinus is vulnerable to be invaded by odontogenic cystic lesions owing to the anatomical relation to the upper alveolar bone. 1 , 2 These lesions usually intrude into the sinus through the inferior and posterior walls. Management of the maxillary sinus diseases is generally via Caldwell-Luc operation or functional endoscopic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Maxillary sinus is vulnerable to be invaded by odontogenic cystic lesions owing to the anatomical relation to the upper alveolar bone. 1 , 2 These lesions usually intrude into the sinus through the inferior and posterior walls. Management of the maxillary sinus diseases is generally via Caldwell-Luc operation or functional endoscopic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…[41]2013N/AN/AImpacted Wisdom ToothMaxillary SinusMaxillary Sinus Pain And Nasal CongestionN/ACT Scan Paranasal SinusesEndoscopicN/AComplete Resolution Of SymptomsN/AAydin Et Al. [42]201621MaleEctopic ToothMaxillary SinusFacial Pain And PressureEndoscopic: Normal Nasal Mucosa.Ct Scan: Completely Opacified Maxillary SinnusOrthopantrogram And CT Scan Paranasal SinusesEndoscopicN/AComplete Resolution Of SymptomsN/AOhki [43]201237MaleImpacted ToothMaxillary SinusNasal Discharge And OdontalgiaCT Scan: Cystic And Calcificated LesionWater’s View X-Ray And CT Scan Paranasal SinusesEndoscopicN/AComplete Resolution Of SymptomsN/AChu And Chiang [44]200349MaleEctopic ToothNasal CavityHard Painful Lesion In Right Nasal FloorN/AN/AEndoscopicN/AComplete Resolution Of SymptomsN/A…”
Section: Resultsmentioning
confidence: 99%
“…Although osteomas are considered benign and there are no reported cases of malignant transformation, they can cause intracranial complications such as mucoceles, meningitis, abscesses, and intraorbital lesions affecting vision [13,14]. Surgery is indicated when the osteoma fills more than 50% of the volume of the maxillary sinus, shows rapid growth, clinical symptoms, chronic sinusitis, facial deformities, bone erosions, or associated complications [15]. The choice of surgical procedure depends on the location, extent, and possible intraoperative complications [16].…”
Section: Discussionmentioning
confidence: 99%
“…Verma et al [5] reported the removal of an osteoma in the maxillary sinus, using the endoscopic technique in conjunction with the extraoral Weber-Ferguson approach. Aydin et al [15] described an osteoma in the maxillary sinus associated with an ectopic tooth, where an uncinectomy and antrostomy were performed to visualize the ectopic tooth, followed by Caldwell-Luc access for osteoma removal.…”
Section: Discussionmentioning
confidence: 99%